PENINGKATAN EFISIENSI PRODUKSI DAN KINERJA LINGKUNGAN MELALUI IMPLEMENTASI PRODUKSI BERSIH DI INDUSTRI KERUPUK SUBUR YOGYAKARTA - , DENOK KUMALASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Subur cracker industry produce solid and liquid wastes which are cause inefficiency production. The liquid waste formed Subur cracker industry activities known have high value of COD and BOD which have potential to cause environmental problems. The aims of this research are to determine the solid wastes that cause the highest dessipation cost, to determine the cleaner production option which can be applied to minimize waste and to evaluate the implementation of cleaner production option. Cleaner production is strategy to minimize wastes and emissions and maximize product output. This research had done by analysing the flow of process production, the material balance in this industry and then to identify cleaner production option to minimize the waste. Cleaner production option were selected to be implemented based on technical, economical and environment feasibility. Evaluation has been done through compared the production efficiency and environment performance before and after implementation. Results of this research shows that the solid waste which caused the highest dessipation cost was dried cracker chips its Rp. 1,344,129.75 per month. The selected cleaner production option was the good house keeping. The cleaner production option to minimize the dried cracker chipâs volume are improving the accuracy of employees, taking the left dough by manual and board layer using. cleaning up the tools and machines before washing process is cleaner production option to minimize the concentration of liquid waste. Implementation of good house keeping option contributes to increase the production efficiency up to 2.75% and increase the environmental performance of COD and BOD as much about 76.67% and 84.00%, respectively.